2022
DOI: 10.1002/hec.4570
|View full text |Cite
|
Sign up to set email alerts
|

The effect of broadband Internet on the gender gap in mental health: Evidence from Germany

Abstract: Mental health conditions, together with substance-use disorders, account for a significant share of the global disease burden (Collins et al., 2011;Vos et al., 2012). This share is particularly large among the population aged 10-24, and has significantly increased over time between 1990 and 2017. 1 Further, women are almost twice as likely as men to experience episodes of depression (DeRubeis et al., 2008; WHO, 2000). The economic costs of poor mental health are large. The World Health Organization estimates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 92 publications
4
19
0
Order By: Relevance
“…Different from these studies, a recent work estimated the causal effect of internet use on residents' depression status ( 47 ), even though causality cannot be fully identified due to a flaw in selected method. Using an instrumental variable-based approach, another work finds a negative effect of internet access on young women's mental health ( 64 ). Our work complements the above strand of literature by measuring depression with a more comprehensive indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Different from these studies, a recent work estimated the causal effect of internet use on residents' depression status ( 47 ), even though causality cannot be fully identified due to a flaw in selected method. Using an instrumental variable-based approach, another work finds a negative effect of internet access on young women's mental health ( 64 ). Our work complements the above strand of literature by measuring depression with a more comprehensive indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Many commentators and researchers have speculated whether it has led to a net benefit for people's emotional and mental well‐being. The paper by Golin (2022) takes on the hugely important question: “What is the effect of access to broadband Internet on mental health?” Her instrumental variables analysis finds that household broadband adoption in Germany led to a statistically significant and economically meaningful deterioration of mental health status for younger adults, driven by effects on women. This important result raises many questions for future research in economics and other disciplines.…”
Section: Causes Of Mental Healthmentioning
confidence: 99%
“…A significant strand of literature has explored the relationship between Internet use and negative affect, such as mental depression, emotional problems, and loneliness (Ding et al, 2022 ; Fan & Yang, 2022 ; Golin, 2022 ; Hökby et al, 2016 ; Nowland et al, 2018 ; Silva et al, 2020 ; Thom et al, 2018 ; Wallinheimo & Evans, 2022 ; Yu et al, 2021 ; Zhang et al, 2022 ). However, the findings are still mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Hökby et al ( 2016 ) found that the magnitude of Internet use among adolescents and young adults is negatively associated with mental health in some European countries, including Estonia, Hungary, Italy, Lithuania, Spain, and Sweden. Golin ( 2022 ) showed that broadband Internet leads to worse mental health for women (primarily those aged 17–30) but not for men in Germany. In contrast, some studies recorded a positive influence of Internet use on health outcomes.…”
Section: Introductionmentioning
confidence: 99%